2018
DOI: 10.1007/s00299-018-2347-9
|View full text |Cite
|
Sign up to set email alerts
|

A specific allele of MYB14 in grapevine correlates with high stilbene inducibility triggered by Al3+ and UV-C radiation

Abstract: Key messageThe structural differences of MYB14 promoter in two grapevine genotypes affect the expression of MYB14 and stilbene synthesis in response to Al3+ and UV-C radiation.AbstractGrapevines provide an important fruit crop worldwide, but production is often limited by pathogen infection. Stilbenes, a class of secondary metabolite, represent phytoalexins that contribute to defence against pathogens in many plants, including grapevine. It is known that the transcription factors MYB14 and MYB15 are required f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 63 publications
(90 reference statements)
1
12
0
Order By: Relevance
“…MDA can be used as a stress indicator, since it is a signal molecule associated with rapid cellular responses during early defense responses (Bai et al 2019). We measured changes in MDA levels and, as shown in Fig.…”
Section: Ros Levels Are Closely Related To Changes In Chlorophyll Andmentioning
confidence: 99%
“…MDA can be used as a stress indicator, since it is a signal molecule associated with rapid cellular responses during early defense responses (Bai et al 2019). We measured changes in MDA levels and, as shown in Fig.…”
Section: Ros Levels Are Closely Related To Changes In Chlorophyll Andmentioning
confidence: 99%
“…In grapevine, STS enzymes mediate the biosynthesis of stilbenes and exhibit broad-spectrum resistance to various pathogens [19]. To explore the molecular mechanisms of V. davidii cv.…”
Section: Resultsmentioning
confidence: 99%
“…Recent research has indicated that ROS not only function as toxic compounds that lead HR, but also act important early signal molecules [30]. Duan et al, proposed that ROS are necessary for the induction of stilbene synthase, and resulted in production of proanthocyanidin [19]. Jiao et al, reported that the accumulation of trans-resveratrol, trans-piceid and cis-piceid markedly increased after treatment with H 2 O 2 [31].…”
Section: Discussionmentioning
confidence: 99%
“…Pre-harvest UV-C treatment can increase the expression levels of FaCHS1 , FaCHI , FaFHT , FaDFR , FaFLS , and FaFGT to promote the accumulation of polyphenols in strawberry fruit [ 42 ]. Stilbene biosynthesis could be promoted by MYB14 under UV-C [ 43 ]. UV-B can affect low molecular weight polyphenol (LMWP) accumulation by promoting DNA methylation to regulate the acclimation mechanisms of plants [ 36 ].…”
Section: Discussionmentioning
confidence: 99%